Public policy in knowledge-based economies : foundations and frameworks - Rooney, David (Cheltenham : Edward Elgar Pub, 2003)
Highlights specific social and cultural conditions that can enhance the communication, use and creation of knowledge in a society. Also illustrates how these social and cultural conditions are identified and analyzed through new conceptual frameworks.
Includes bibliographical references and index.
oif 07/04/15
Loan
Keywords: Information policy; Knowledge, Sociology of; Political planning; Information society; Knowledge management